2015
DOI: 10.1038/ncomms8075
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Ndd1 by APC/CCdh1 generates a feed forward loop that times mitotic protein accumulation

Abstract: Ndd1 activates the Mcm1-Fkh2 transcription factor to transcribe mitotic regulators. The anaphase-promoting complex/cyclosome activated by Cdh1 (APC/C Cdh1 ) mediates the degradation of proteins throughout G1. Here we show that the APC/C Cdh1 ubiquitinates Ndd1 and mediates its degradation, and that APC/C Cdh1 activity suppresses accumulation of Ndd1 targets. We confirm putative Ndd1 targets and identify novel ones, many of them APC/C Cdh1 substrates. The APC/C Cdh1 thus regulates these proteins in a dual manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 70 publications
(71 reference statements)
0
18
0
Order By: Relevance
“…Indeed, it has been shown that the activity of Hcm1 is regulated by CDK phosphorylation (Landry et al, 2014). On the other hand, Nrm1, Yhp1, and Ndd1 appear to be substrates of APC Cdh1 (Edenberg et al, 2015; Ostapenko and Solomon, 2011; Sajman et al, 2015), which is an E3 ubiquitin ligase complex normally inactivated at G1/S transition by CDK phosphorylation (Huang et al, 2001; Jaspersen et al, 1999; Yeong et al, 2001; Zachariae et al, 1998). If Cdh1 is normally inactivated by CDK at the G1/S border, then the cdc28-4 mutant cells should have constitutively active APC Cdh1 , and thus APC Cdh1 substrates might not accumulate at the protein level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been shown that the activity of Hcm1 is regulated by CDK phosphorylation (Landry et al, 2014). On the other hand, Nrm1, Yhp1, and Ndd1 appear to be substrates of APC Cdh1 (Edenberg et al, 2015; Ostapenko and Solomon, 2011; Sajman et al, 2015), which is an E3 ubiquitin ligase complex normally inactivated at G1/S transition by CDK phosphorylation (Huang et al, 2001; Jaspersen et al, 1999; Yeong et al, 2001; Zachariae et al, 1998). If Cdh1 is normally inactivated by CDK at the G1/S border, then the cdc28-4 mutant cells should have constitutively active APC Cdh1 , and thus APC Cdh1 substrates might not accumulate at the protein level.…”
Section: Resultsmentioning
confidence: 99%
“…We excluded the cluster containing CDC20 that exhibited an early minor peak in the wild type datasets to avoid complex regulations by factors other than SFF. The remaining cluster contains 17 genes that partially overlapped with previously reported CLB2 cluster or SFF targets (Sajman et al, 2015; Spellman et al, 1998; Zhu et al, 2000).…”
Section: Methodsmentioning
confidence: 90%
“…The mRNAs encoding many APC substrates in yeast are also cell cycle regulated, with synthesis of their corresponding proteins peaking following the mRNA expression peak [75][76][77]. In fact, transcription factors that transcribe yeast APC substrates, such as Fkh1 [29] and Ndd1 [78], are targeted by the APC, thereby creating feedforward loops. This loop is further layered by the observation that the yeast Fkh2 transcription factor (also likely an APC target; our unpublished observation) recruits Ndd1 to chromatin of additional G2/M specific APC subunit promoters [79].…”
Section: Discussionmentioning
confidence: 99%
“…We excluded the cluster containing CDC20 that exhibited an early minor peak in the wild type datasets to avoid complex regulations by factors other than SFF. The remaining cluster contains 17 genes that partially overlapped with previously reported CLB2 cluster or SFF targets [1,34,66].…”
Section: Compilation Of Canonical Targets Of the Tf Networkmentioning
confidence: 91%
“…Indeed, it has been shown that the activity of Hcm1 is regulated by CDK phosphorylation [31]. On the other hand, Nrm1, Yhp1, and Ndd1 appear to be substrates of APC Cdh1 [32][33][34], which is an E3 ubiquitin ligase complex normally inactivated at G1/S transition by CDK phosphorylation [35][36][37][38]. If Cdh1 is normally inactivated by CDK at the G1/S border, then the cdc28-4 mutant cells should have constitutively active APC Cdh1 , and thus APC Cdh1 substrates might not accumulate at the protein level.…”
Section: Anaphase-promoting Complex (Apc) Prevents the Accumulation Omentioning
confidence: 99%